Queer and Bookish Eve Kosofsky Sedgwick as Book Artist - Edwards, Jason (punctum books, 2022)
Queer and Bookish: Eve Kosofksy Sedgwick as Book Artist represents the first book-length study to explore the intersections of Sedgwick's critical writing, poetry, and, most importantly, book art, making the case that her art criticism, especially her meditations on domestic and nineteenth-century photography, and "artist's book" projects are as formally complex and brilliant, conceptually significant and life-changing, as her literary criticism and theory. In addition, the book represents a significant intervention into recent debates about reparative reading, surface reading, and the descriptive turn across the humanities, because of its sustained, positive accounts on Sedgwick's books as visual, textural, and material objects. The book ranges across Sedgwick's published output, from The Coherence of Gothic Conventions (1980) to the posthumously published The Weather in Proust (2011), and features her meditations on a wide variety of art-historical topoi, including Judith Scott's queer/crip fiber art; the anality of Polykleitos's Doryphorus; queer Modernist typography; Piranesi's punitive space; Duncan Grant and Vanessa Bell's queer holy family; Manet's frontality and thalassic aesthetics; fat and thin aesthetics of various stripes; and the queer photography of Anna Atkins, Clementina Hawarden, and Julia Margaret Cameron; Baron De Mayer, Eugene Atget, and P.H. Emerson; as well as David Hockney, Ken Brown, and her own father, a NASA lunar photographer. The book climaxes with two chapter-length explorations of Sedgwick's own late-life book-art practice: her panda Valentine alphabet cards (c. 1996) and her Last Days of Pompeii/Cavafy unique artist's book (c. 2007).